ANCAMAN SPIONASE DALAM PENGGUNAAN WHATSAPP DI BIDANG PERTAHANAN INDONESIA - Abdul Razzaq Matthew Aditya (Jurnal Imagine, 2023)
WhatsApp is a popular instant messaging app among Indonesians, but its data security and login access system have been a major concern. The vulnerability of the security system has led to an increase in cyber practices that can harm WhatsApp users, including espionage. The aim of this study is to identify the potential for espionage using WhatsApp in the virtual world. The research method used in this study was a literature review, including journals, articles, news, and websites related to espionage and WhatsApp. The findings of this study indicate that espionage is a cybercrime used as a military strategy to steal political, economic, and military information. Additionally, WhatsApp is one of the most widely used instant messaging apps among Indonesians and ranks second in terms of usage. Thirdly, potential espionage on the WhatsApp application includes spyware planting, hacking through calls, MP4 video formats, URL links, photo filter features, and malware planted through phone numbers, known as Pegasus spyware. Spyware Pegasus attacks the zero-day system of iOS and Android systems and smartphone applications, including the WhatsApp application currently used by Indonesian government agencies as a communication and work media. Finally, prevention measures that can be taken include protecting information, ensuring existing security measures, and planning for risks and threats